EVALUATION THE ACTIVITY OF MYRTUS . COMMUNIS ANDNIGELLA. SATIVA PLANT EXTRACT ON THE VIABILITY OFECHINOCOCCUS PROTOSCOLICES:IN VITRO STUDY - Al-Basheer, Nada; Al- Marsome, Huda; Al –azawi, Bader (Iraqi Journal of Science, 2024)
This study was aimed to treat the hydatid disease that caused by the larval stage ofEchinococcus granulosus using two water plant extracts (leaves of Myrtus communis,seeds of Nigella sativa). The effect of these extracts had been studied on the viability ofE. granulosus protoscolices in vitro using five concentrations of each of them rangingbetween ( 30,35,40,45,50)mgfor the plants extracts, The preliminary results revealedthat M. communis extract was the most effective in killing the protoscolices in vitr thanN.sativa in comparison to the control group.